PENGARUH INTERAKSI SUPPORTER DENGAN MANAJEMEN CLUB PERSEBAYA TERHADAP PENGUKURAN KINERJA MANAJEMEN CLUB PERSEBAYA - Rahayuningsih, Sri; Prihastuty, Dyah Rini (JEM17: Jurnal Ekonomi Manajemen, 2021)
Persebaya supporters are called Bonek Mania, Bonek is one of the most fanatical supporters in Indonesia, almost all Persebaya Bonek matches are always present to provide total support. During the Persebaya Bonek match, not only Surabaya, but also Sidoarjo, Pasuruan, Gresik, and several supporting cities of Surabaya. The purpose of this study was to provide answers and explanations to the questions or problems previously raised, namely, to analyze the effect of partial supporter interaction on the performance of Persebaya club management. This study uses a quantitative approach and aims to determine the effect of the interaction of supporters and club management Persebaya on improving club management performance and improving the quality of club management Persebaya. The data collection technique is through a questionnaire distributed to respondents in the form of a google form to be filled in according to the situation.